2015
DOI: 10.1007/s10854-015-3102-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gallium addition in Sn–Ag–Cu lead-fee solder

Abstract: Sn-Ag-Cu based alloys are a series of important candidates of lead-free solders. However the melting temperatures are still higher than the traditional Sn-Pb solder. Gallium (Ga) is one of the candidate elements to be alloyed with the Sn-Ag-Cu solder. The present work aims at investigating the influence of Ga addition (\1.5 wt%) on properties of the Sn-Ag-Cu alloys, e.g. melting performance, wetting behaviour, formation of intermetallic compounds on the interface, and shear strength of the solder joints. When … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Also, small addition of gallium to the Ag‐Cu‐Sn lead‐free solder were introduced to lower the melting points and change the wettability of this solder. [ 9 ] Unfortunately, many important technical challenges need to be addressed before they can be successfully applied to solder. The mechanical behavior and reliability of Ag‐Cu‐Ga solder joints may be significantly controlled by these two IMCs (Ag 2 Ga and CuGa 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, small addition of gallium to the Ag‐Cu‐Sn lead‐free solder were introduced to lower the melting points and change the wettability of this solder. [ 9 ] Unfortunately, many important technical challenges need to be addressed before they can be successfully applied to solder. The mechanical behavior and reliability of Ag‐Cu‐Ga solder joints may be significantly controlled by these two IMCs (Ag 2 Ga and CuGa 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Also, small additions of gallium to the Ag-Cu-Sn lead-free solder were introduced to lower the melting points and to change wettability of this solder. [5] As far as solid gallium alloys are concerned, it was found that gallium addition to gold results in bright-blue color, which is exploited in jewelry. [6][7][8] Addition of gallium into gold-palladium and copper-palladium alloys led to the production of a new type of fillings in dentistry.…”
Section: Introductionmentioning
confidence: 99%
“…The Ga atoms dissolved into the melting solder matrix which eventually caused the spreading ratio to increase. Higher content of Ga in the solders (above 2wt%) resulted in change of lattice parameters of solders and substrates, increasing the coherency of interface (Chen, Guo, Huang & Wang, 2015).…”
Section: On the Wettability Of Sn-ga Soldersmentioning
confidence: 99%